Forensic social work: psychosocial and legal issues in diverse practice settings - Maschi, Tina (Springer, 2009)
Defining collaborative forensic social work with diverse populations / Tina Maschi and Mary Lou Killian -- A history of forensic social work in the United States / Mary Lou Killian and Tina Maschi -- Visualizing forensic social work and collaborative practice : a social justice systems approach / Tina Maschi and Mary Lou Killian -- Understanding civil and criminal law / Christine Heer -- From intervention roles to multidisciplinary practice / Laura Kelly, Nora Smith, Sandy Gibson -- Family : youth & adults / Nancy Mezey and Rebecca Sanford -- Social services : meeting basic human needs of income, food, and shelter / Ann Sparks -- Special topic : assisting female victims of intimate partner violence : the role of victim advocates / Marie Mele -- Special topic : forensic practice with older adults victims of abuse / Janet Mahoney and Morris Saldov -- Social work, education, and the law / Carolyn Bradley, Rosemary Richards, Jean Doyle -- Special topic : building bridges : school reentry of incarcerated juveniles / Lauri Goldkind and Paul Hirschfield -- Child welfare / Nora Smith -- Special topic : forensic interviewing for child sexual abuse / Kenneth Lau and Eileen Treacy -- Mental health and addictions settings : legal and ethical issues for practice / Carolyn Bradley and Kelly Ward -- Special topic : "order in the drug court" : understanding the intersection of substance abuse and law / Keith Morgen, Lauren Gunneson, and Lisa Maietta -- Special topic : women at risk : legal involvement among mothers in addiction treatment / Nancy M. Violette, Thomas J. Morgan, & Audrey Redding-Raines -- Special topic : suicide prevention programming in the jail setting / Schnavia Smith Hatcher -- Juvenile justice and social work / Tina Maschi, Nancy Violette, Jennifer Ristow, Nancy Scotto Rosato -- Criminal justice : prisons as a practice setting / Rebecca Sanford and Johana Foster -- Criminal justice : reentry in the twenty-first century / Patricia O'Brien -- Special topic : disproportionate involvement of minority youth / Leon Banks, Schnavia Smith Hatcher, Ed Risler -- Special topic : restorative justice : what social workers need to know / Katherine van Wormer -- Human rights : implications for forensic social work / Rosemary Barbera -- Calling some "illegal" : practice considerations in work with undocumented immigrants / Carol Cleaveland -- Collaborative forensic social work with refugees / Mary Kay Jou and Leah Lazzaro -- Human rights issues and research with prisoners and other vulnerable populations : where does evidence-based practices go from here? / Sandy Gibson